THE VASCULAR SURGERY EMERGENCY DEPARTMENT IN TIMES OF COVID-19 PANDEMIC - Rocha, Henrique (2021)
Background: The surge of the COVID-19 pandemic in Portugal and the implemented public health measures were accompanied with a noticeable decrease in patients’ attendance to the Emergency Department (ED). Objectives: This study aims to evaluate the impact of COVID-19 pandemic on Vascular Surgery ED admissions, by comparing clinical and demographic characteristics of patients visiting the ED during the pandemic and the homologous period of 2019. Methods: We retrospectively collected data from patients admitted to the ED of a Portuguese tertiary hospital centre between March 4th and April 1st, 2020 — two weeks before and two weeks after the governmental implementation of the state of emergency in our country due to the COVID-19 pandemic — and the homologous period of 2019. Individual medical records were revised to obtain patients demographics and characteristics, clinical severity under the Manchester Triage System (MTS), final diagnosis, need for hospitalization or emergent/urgent surgery, in-hospital length of stay and mortality within 30 days of hospital discharge. Results: A total of 119 and 210 patients visited the Vascular Surgery ED during the pandemic and the homologous period of 2019, respectively. Males comprised the majority of patients in both years and the proportion of women visiting the ED was lower in 2020 compared to 2019 (P=0.015). The MTS attributed a lower number of high-priority levels (yellow and orange) to patients visiting the ED in 2020 (P=0.048). A higher proportion of patients required in-hospital treatment or emergent/ urgent surgery (P<0.001 and P=0.002, respectively) during the pandemic. No differences were observed in in-hospital length of stay and early mortality. The most prevalent diagnosis during this critical period were chronic limb threatening ischemia (CLTI), deep vein thrombosis, and acute limb ischemia; in 2019, CLTI, non-vascular limb pain and post-operative pain were the dominating diagnosis. Conclusion: We found a 43.3% decrease in the number of visits to the Vascular Surgery ED in the first month after the inaugural diagnosis of COVID-19 in Portugal. There was a significant reduction of patients with high-priority complaints, but those who presented to the ED had more severe and advanced disease, reflected by the increased proportion on hospitalization and emergent/urgent surgery requirements. Fear of infection and mobility limitations imposed by the quarantine may deter patients from attending the ED and delay proper healthcare. Mid to long-term impact of such behaviour on morbimortality should be determined to evaluate the quality of response of healthcare services to the pandemic.